Epikureanisme dan Stoikisme: Etika Helenistik untuk Seni Hidup Modern - Michael Carlos Kodoati (Sekolah Tinggi Filsafat Seminari Pineleng, 2023)
This writing aims to observe the inheritance of Hellenistic Ethics for Modern Ethics. Through literature research, Epicureanism and Stoicism, two major contradicted Hellenistic movements, are used to look for how modern people get happiness. Epicureanism and Stoicism are both in tension to answer the question about what people find in themselves. Aristotle answered this finding with the idea of eudaimonia. Therefore, ethics for pursuing happiness in modern life might be seen as the art of living, as Hellenistic wisdom lived out differently, either Epicureanism or Stoicism. Both are contradictory, yet offer the value of how life must be carried out such as making a craft, in the sense of tekne or